2015
DOI: 10.1371/journal.pone.0119014
|View full text |Cite
|
Sign up to set email alerts
|

The Network of Antigen-Antibody Reactions in Adult Women with Breast Cancer or Benign Breast Pathology or without Breast Pathology

Abstract: The Immunoglobulin G (IgG) antibody response to different protein antigens of the mammary ductal carcinoma by adult women affected by Breast Cancer (BC) distinguishes at least 103 proteins that differ in their molecular weights (MW). The IgG producing cell clones (nodes) coexist with each other in each individual organism and share energy resources among themselves, as well as factors that control the level of expression and Specificity of their IgG antibodies. So, it can be proposed that among them there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In a previous study, we showed, on the one hand, that the number of serum proteins recognized by autoantibodies increases in BC patients as compared with BBP patients or H women ( Romo-González et al., 2015 ). On the other hand, the inter-individuals variability of these protein profiles was significantly less in BC patients than BBP patients or H women.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a previous study, we showed, on the one hand, that the number of serum proteins recognized by autoantibodies increases in BC patients as compared with BBP patients or H women ( Romo-González et al., 2015 ). On the other hand, the inter-individuals variability of these protein profiles was significantly less in BC patients than BBP patients or H women.…”
Section: Discussionmentioning
confidence: 89%
“…Both sets of observations, confirmed in the present study, suggest that even though BC patients seem to release a higher number of antigenic proteins and/or a greater number of autoimmune B-lymphocyte clones, the immune-serological response is much more homogeneous in BC patients than that demonstrated by BBP patients and healthy women. From a network analysis standpoint, this would mean that the network in BC patients is weak, as compared with the BBP patient or H women's networks, by decreasing the connectivity established toward a handful of hubs, represented here by the identifying high-risk protein bands, even though the number of nodes increases ( Albert and Barabasi, 2000 ; Romo-González et al., 2015 ). In support of these contentions stands the fact that the number of nodes receiving between 19 and 24 connections (hubs) was significantly lower in women diagnosed with BC than in those with BBP or considered to be healthy ( Romo-González et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast cancer is the most common cancer among women in developing country (Delort, et al, 2015, Engels, et al, 2015. This is responsible for many deaths in worldwide (Romo-Gonzalez, et al, 2015). Treatment consists of surgery, radiotherapy, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%